Unsaturated fat intakes and mental health outcomes in young women from the Australian Longitudinal Study on Women's Heath. Issue 3 (29th April 2014) - Daley, Clare; Patterson, Amanda; Sibbritt, David; MacDonald-Wicks, Lesley
Abstract Objective To determine if associations exist between a range of unsaturated fatty acid intakes and mental health outcomes. Design Cross-sectional data analysis of the Australian Longitudinal Study on Women's Health (ALSWH) Young Cohort Survey 3 that included the validated seventy-four-item Dietary Questionnaire for Epidemiological Studies FFQ, validated mental health scales and self-report questions on depression and anxiety. Setting Australia, 2003. Subjects A nationally representative sample of young Australian women (25–30 years) from ALSWH. The 7635 women with plausible energy intakes (>4·5 but <20·0 MJ/d) were included in the analyses. Results Adjusted logistic regression analyses found statistically significant associations between higher intakes of α-linolenic acid and decreased likelihood of depressive symptoms indicated by the ten-item Center for Epidemiological Studies Depression Scale (CESD-10; OR=0·77; 95 % CI 0·60, 0·99; P=0·040) and the Short Form Health Survey (SF-36) mental health subscale (OR=0·73 95 % CI 0·56, 0·96; P=0·024). Furthermore, higher intakes of n-6 fatty acids (OR=0·96, 95 % CI 0·93, 0·99; P=0·019) and linoleic acid (OR=0·96, 95 % CI 0·93, 0·99; P=0·020) were associated with decreased likelihood of self-reported diagnosed anxiety and higher intakes of n-9 fatty acids (OR=1·02, 95 % CI 1·00, 1·04; P=0·041) and oleic acid (OR=1·02, 95 % CI 1·00, 1·05; P=0·046) were associated with increased likelihood of self-reported diagnosed anxiety. Conclusions: Increased intakes of α-linolenic acid were associated with a reduced likelihood of depressive symptoms, increased intakes of n-6 fatty acids and linoleic acid were associated with a reduced likelihood of self-reported anxiety, and increased intakes of n-9 fatty acids and oleic acid were associated with an increased likelihood of anxiety. Additional studies are needed to further elucidate associations between unsaturated fatty acids and depression and anxiety.